An Analysis of Cinematographic Elements in The Film Autobiography - Semesta, Cakrawala Jagad; Ersyad, Firdaus Anwar; Sintowoko, Dyah Ayu Wiwid (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
The film “Autobiography” was inspired by the director's own experience and dissatisfaction with a system that imposed strict adherence to norms. The objective of this study is to examine the cinematographic components of the film titled “Autobiography”. This study employs a qualitative approach to observation, utilising cinematographic theory and the Blain Brown technique to examine and analyse autobiographical videos. The analysis focuses on three key elements of cinematographic theory: frame, light, colour, and movement. The findings of this study demonstrate that the film use the frame-within-frame approach to portray a more self-absorbed character. Additionally, the film utilises numerous close-up shots and low-angle techniques to depict a more amiable figure. The film utilises practical components and natural light extensively in its lighting design, creating a heightened sense of realism that enhances the audience's immersion. This picture employs a dark colour palette to enhance its air of mystery. This is demonstrated by the transition of the colour sign from green to red. The camera movement techniques of stationary, tracking, countermove, reveal, zoom in, and tilting up/down are employed to provide dramatic and stressful components in the process of capturing photographs.